LOCAL ECONOMIC TRANSFORMATION: LITERATURE ANALYSIS AND STRATEGIES FOR COMMUNITY ECONOMIC CAPACITY BUILDING - Moh. Yamin Darsyah; Maulana Arafat Lubis; Nashran Azizan; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2023)
Strategies that successfully enhance the economic capacity of communities have high relevance in the current context of globalisation and digital transformation. With the rapid growth of technology and changes in the structure of the labour market, an in-depth understanding of effective methods to promote economic and social development is needed. The study conducted in this research uses the literature research method. The results show that investment in human capital development through education and training that matches the needs of the labour market is fundamental in increasing economic capacity. Infrastructure modernisation, which includes the development of physical and digital facilities, supports the efficiency of business operations and expands market reach. In addition, strategies that support the innovation ecosystem by facilitating collaboration between sectors encourage the development of new technologies and improve competitiveness. As a result, these strategies contribute to inclusive and sustainable economic growth.